/** * @license Apache-2.0 * * Copyright (c) 2018 The Stdlib Authors. * * Licensed under the Apache License, Version 2.0 (the "License"); * you may not use this file except in compliance with the License. * You may obtain a copy of the License at * * http://www.apache.org/licenses/LICENSE-2.0 * * Unless required by applicable law or agreed to in writing, software * distributed under the License is distributed on an "AS IS" BASIS, * WITHOUT WARRANTIES OR CONDITIONS OF ANY KIND, either express or implied. * See the License for the specific language governing permissions and * limitations under the License. */ 'use strict'; // MODULES // var isPositiveInteger = require( '@stdlib/assert/is-positive-integer' ).isPrimitive; var isNumber = require( '@stdlib/assert/is-number' ).isPrimitive; var isnan = require( '@stdlib/math/base/assert/is-nan' ); var Float64Array = require( '@stdlib/array/float64' ); // MAIN // /** * Returns an accumulator function which incrementally computes a moving unbiased sample covariance. * * ## Method * * - Let \\(W\\) be a window of \\(N\\) elements over which we want to compute an unbiased sample covariance. * * - We begin by defining the covariance \\( \operatorname{cov}_n(x,y) \\) for a window \\(n\\) as follows * * ```tex * \operatorname{cov}_n(x,y) &= \frac{C_n}{n} * ``` * * where \\(C_n\\) is the co-moment, which is defined as * * ```tex * C_n = \sum_{i=1}^{N} ( x_i - \bar{x}_n ) ( y_i - \bar{y}_n ) * ``` * * and where \\(\bar{x}_n\\) and \\(\bar{y}_n\\) are the sample means for \\(x\\) and \\(y\\), respectively, and \\(i=1\\) specifies the first element in a window. * * - The sample mean is computed using the canonical formula * * ```tex * \bar{x}_n = \frac{1}{N} \sum_{i=1}^{N} x_i * ``` * * which, taking into account a previous window, can be expressed * * ```tex * \begin{align*} * \bar{x}_n &= \frac{1}{N} \biggl( \sum_{i=0}^{N-1} x_i - x_0 + x_N \biggr) \\ * &= \bar{x}_{n-1} + \frac{x_N - x_0}{N} * \end{align*} * ``` * * where \\(x_0\\) is the first value in the previous window. * * - We can substitute into the co-moment equation * * ```tex * \begin{align*} * C_n &= \sum_{i=1}^{N} ( x_i - \bar{x}_n ) ( y_i - \bar{y}_n ) \\ * &= \sum_{i=1}^{N} \biggl( x_i - \bar{x}_{n-1} - \frac{x_N - x_0}{N} \biggr) \biggl( y_i - \bar{y}_{n-1} - \frac{y_N - y_0}{N} \biggr) \\ * &= \sum_{i=1}^{N} \biggl( \Delta x_{i,n-1} - \frac{x_N - x_0}{N} \biggr) \biggl( \Delta y_{i,n-1} - \frac{y_N - y_0}{N} \biggr) * \end{align*} * ``` * * where * * ```tex * \Delta x_{i,k} = x_i - \bar{x}_{k} * ``` * * - We can subsequently expand terms and apply a summation identity * * ```tex * \begin{align*} * C_n &= \sum_{i=1}^{N} \Delta x_{i,n-1} \Delta y_{i,n-1} - \sum_{i=1}^{N} \Delta x_{i,n-1} \biggl( \frac{y_N - y_0}{N} \biggr) - \sum_{i=1}^{N} \Delta y_{i,n-1} \biggl( \frac{x_N - x_0}{N} \biggr) + \sum_{i=1}^{N} \biggl( \frac{x_N - x_0}{N} \biggr) \biggl( \frac{y_N - y_0}{N} \biggr) \\ * &= \sum_{i=1}^{N} \Delta x_{i,n-1} \Delta y_{i,n-1} - \biggl( \frac{y_N - y_0}{N} \biggr) \sum_{i=1}^{N} \Delta x_{i,n-1} - \biggl( \frac{x_N - x_0}{N} \biggr) \sum_{i=1}^{N} \Delta y_{i,n-1} + \frac{(x_N - x_0)(y_N - y_0)}{N} * \end{align*} * ``` * * - Let us first consider the second term which we can reorganize as follows * * ```tex * \begin{align*} * \biggl( \frac{y_N - y_0}{N} \biggr) \sum_{i=1}^{N} \Delta x_{i,n-1} &= \biggl( \frac{y_N - y_0}{N} \biggr) \sum_{i=1}{N} ( x_i - \bar{x}_{n-1}) \\ * &= \biggl( \frac{y_N - y_0}{N} \biggr) \sum_{i=1}^{N} x_i - \biggl( \frac{y_N - y_0}{N} \biggr) \sum_{i=1}^{N} \bar{x}_{n-1} \\ * &= (y_N - y_0) \bar{x}_{n} - (y_N - y_0)\bar{x}_{n-1} \\ * &= (y_N - y_0) (\bar{x}_{n} - \bar{x}_{n-1}) \\ * &= \frac{(x_N - x_0)(y_N - y_0)}{N} * \end{align*} * ``` * * - The third term can be reorganized in a manner similar to the second term such that * * ```tex * \biggl( \frac{x_N - x_0}{N} \biggr) \sum_{i=1}^{N} \Delta y_{i,n-1} = \frac{(x_N - x_0)(y_N - y_0)}{N} * ``` * * - Substituting back into the equation for the co-moment * * ```tex * \begin{align*} * C_n &= \sum_{i=1}^{N} \Delta x_{i,n-1} \Delta y_{i,n-1} - \frac{(x_N - x_0)(y_N - y_0)}{N} - \frac{(x_N - x_0)(y_N - y_0)}{N} + \frac{(x_N - x_0)(y_N - y_0)}{N} \\ * &= \sum_{i=1}^{N} \Delta x_{i,n-1} \Delta y_{i,n-1} - \frac{(x_N - x_0)(y_N - y_0)}{N} * \end{align*} * ``` * * - Let us now consider the first term which we can modify as follows * * ```tex * \begin{align*} * \sum_{i=1}^{N} \Delta x_{i,n-1} \Delta y_{i,n-1} &= \sum_{i=1}^{N} (x_i - \bar{x}_{n-1})(y_i - \bar{y}_{n-1}) \\ * &= \sum_{i=1}^{N-1} (x_i - \bar{x}_{n-1})(y_i - \bar{y}_{n-1}) + (x_N - \bar{x}_{n-1})(y_N - \bar{y}_{n-1}) \\ * &= \sum_{i=1}^{N-1} (x_i - \bar{x}_{n-1})(y_i - \bar{y}_{n-1}) + (x_N - \bar{x}_{n-1})(y_N - \bar{y}_{n-1}) + (x_0 - \bar{x}_{n-1})(y_0 - \bar{y}_{n-1}) - (x_0 - \bar{x}_{n-1})(y_0 - \bar{y}_{n-1}) \\ * &= \sum_{i=0}^{N-1} (x_i - \bar{x}_{n-1})(y_i - \bar{y}_{n-1}) + (x_N - \bar{x}_{n-1})(y_N - \bar{y}_{n-1}) - (x_0 - \bar{x}_{n-1})(y_0 - \bar{y}_{n-1}) * \end{align*} * ``` * * where we recognize that the first term equals the co-moment for the previous window * * ```tex * C_{n-1} = \sum_{i=0}^{N-1} (x_i - \bar{x}_{n-1})(y_i - \bar{y}_{n-1}) * ``` * * In which case, * * ```tex * \begin{align*} * \sum_{i=1}^{N} \Delta x_{i,n-1} \Delta y_{i,n-1} &= C_{n-1} + (x_N - \bar{x}_{n-1})(y_N - \bar{y}_{n-1}) - (x_0 - \bar{x}_{n-1})(y_0 - \bar{y}_{n-1}) \\ * &= C_{n-1} + \Delta x_{N,n-1} \Delta y_{N,n-1} - \Delta x_{0,n-1} \Delta y_{0,n-1} * \end{align*} * ``` * * - Substituting into the equation for the co-moment * * ```tex * C_n = C_{n-1} + \Delta x_{N,n-1} \Delta y_{N,n-1} - \Delta x_{0,n-1} \Delta y_{0,n-1} - \frac{(x_N - x_0)(y_N - y_0)}{N} * ``` * * - We can make one further modification to the last term * * ```tex * \begin{align*} * \frac{(x_N - x_0)(y_N - y_0)}{N} &= \frac{(x_N - \bar{x}_{n-1} - x_0 + \bar{x}_{n-1})(y_N - \bar{y}_{n-1} - y_0 + \bar{y}_{n-1})}{N} \\ * &= \frac{(\Delta x_{N,n-1} - \Delta x_{0,n-1})(\Delta y_{N,n-1} - \Delta y_{0,n-1})}{N} * \end{align*} * ``` * * which, upon substitution into the equation for the co-moment, yields * * ```tex * C_n = C_{n-1} + \Delta x_{N,n-1} \Delta y_{N,n-1} - \Delta x_{0,n-1} \Delta y_{0,n-1} - \frac{(\Delta x_{N,n-1} - \Delta x_{0,n-1})(\Delta y_{N,n-1} - \Delta y_{0,n-1})}{N} * ``` * * * @param {PositiveInteger} W - window size * @param {number} [meanx] - mean value * @param {number} [meany] - mean value * @throws {TypeError} first argument must be a positive integer * @throws {TypeError} second argument must be a number primitive * @throws {TypeError} third argument must be a number primitive * @returns {Function} accumulator function * * @example * var accumulator = incrmcovariance( 3 ); * * var v = accumulator(); * // returns null * * v = accumulator( 2.0, 1.0 ); * // returns 0.0 * * v = accumulator( -5.0, 3.14 ); * // returns ~-7.49 * * v = accumulator( 3.0, -1.0 ); * // returns -8.35 * * v = accumulator( 5.0, -9.5 ); * // returns -29.42 * * v = accumulator(); * // returns -29.42 * * @example * var accumulator = incrmcovariance( 3, -2.0, 10.0 ); */ function incrmcovariance( W, meanx, meany ) { var buf; var dx0; var dxN; var dy0; var dyN; var mx; var my; var wi; var C; var N; var n; var i; if ( !isPositiveInteger( W ) ) { throw new TypeError( 'invalid argument. First argument must be a positive integer. Value: `' + W + '`.' ); } buf = new Float64Array( 2*W ); // strided array n = W - 1; C = 0.0; wi = -1; N = 0; if ( arguments.length > 1 ) { if ( !isNumber( meanx ) ) { throw new TypeError( 'invalid argument. Second argument must be a number primitive. Value: `' + meanx + '`.' ); } if ( !isNumber( meany ) ) { throw new TypeError( 'invalid argument. Third argument must be a number primitive. Value: `' + meany + '`.' ); } mx = meanx; my = meany; return accumulator2; } mx = 0.0; my = 0.0; return accumulator1; /** * If provided a value, the accumulator function returns an updated unbiased sample covariance. If not provided a value, the accumulator function returns the current unbiased sample covariance. * * @private * @param {number} [x] - input value * @param {number} [y] - input value * @returns {(number|null)} unbiased sample covariance or null */ function accumulator1( x, y ) { var v1; var v2; var k; var j; if ( arguments.length === 0 ) { if ( N === 0 ) { return null; } if ( N === 1 ) { return 0.0; } if ( N < W ) { return C / (N-1); } return C / n; } // Update the window and strided array indices for managing the circular buffer: wi = (wi+1) % W; i = 2 * wi; // Case: an incoming value is NaN, the sliding co-moment is automatically NaN... if ( isnan( x ) || isnan( y ) ) { N = W; // explicitly set to avoid `N < W` branch C = NaN; } // Case: initial window... else if ( N < W ) { buf[ i ] = x; // update buffer buf[ i+1 ] = y; N += 1; dxN = x - mx; mx += dxN / N; my += ( y-my ) / N; C += dxN * ( y-my ); // Note: repeated `y-my` is intentional, as `my` is updated when used here if ( N === 1 ) { return 0.0; } return C / (N-1); } // Case: N = W = 1 else if ( N === 1 ) { return 0.0; } // Case: an outgoing value is NaN, and, thus, we need to compute the accumulated values... else if ( isnan( buf[ i ] ) || isnan( buf[ i+1 ] ) ) { N = 1; mx = x; my = y; C = 0.0; for ( k = 0; k < W; k++ ) { j = 2 * k; // convert to a strided array index if ( j !== i ) { v1 = buf[ j ]; v2 = buf[ j+1 ]; if ( isnan( v1 ) || isnan( v2 ) ) { N = W; // explicitly set to avoid `N < W` branch C = NaN; break; // co-moment is automatically NaN, so no need to continue } N += 1; dxN = v1 - mx; mx += dxN / N; my += ( v2-my ) / N; C += dxN * ( v2-my ); // Note: repeated `y-my` is intentional, as `my` is updated when used here } } } // Case: neither the current co-moment nor the incoming values are NaN, so we need to update the accumulated values... else if ( isnan( C ) === false ) { dx0 = buf[ i ] - mx; dy0 = buf[ i+1 ] - my; dxN = x - mx; dyN = y - my; C += (dxN*dyN) - (dx0*dy0) - ( (dxN-dx0)*(dyN-dy0)/W ); mx += ( dxN-dx0 ) / W; my += ( dyN-dy0 ) / W; } // Case: the current co-moment is NaN, so nothing to do until the buffer no longer contains NaN values... buf[ i ] = x; buf[ i+1 ] = y; return C / n; } /** * If provided a value, the accumulator function returns an updated unbiased sample covariance. If not provided a value, the accumulator function returns the current unbiased sample covariance. * * @private * @param {number} [x] - input value * @param {number} [y] - input value * @returns {(number|null)} unbiased sample covariance or null */ function accumulator2( x, y ) { var k; var j; if ( arguments.length === 0 ) { if ( N === 0 ) { return null; } if ( N < W ) { return C / N; } return C / W; } // Update the window and strided array indices for managing the circular buffer: wi = (wi+1) % W; i = 2 * wi; // Case: an incoming value is NaN, the sliding co-moment is automatically NaN... if ( isnan( x ) || isnan( y ) ) { N = W; // explicitly set to avoid `N < W` branch C = NaN; } // Case: initial window... else if ( N < W ) { buf[ i ] = x; // update buffer buf[ i+1 ] = y; N += 1; C += ( x-mx ) * ( y-my ); return C / N; } // Case: an outgoing value is NaN, and, thus, we need to compute the accumulated values... else if ( isnan( buf[ i ] ) || isnan( buf[ i+1 ] ) ) { C = 0.0; for ( k = 0; k < W; k++ ) { j = 2 * k; // convert to a strided array index if ( j !== i ) { if ( isnan( buf[ j ] ) || isnan( buf[ j+1 ] ) ) { N = W; // explicitly set to avoid `N < W` branch C = NaN; break; // co-moment is automatically NaN, so no need to continue } C += ( buf[j]-mx ) * ( buf[j+1]-my ); } } } // Case: neither the current co-moment nor the incoming values are NaN, so we need to update the accumulated values... else if ( isnan( C ) === false ) { // Use textbook formula along with simplification arising from difference of sums: C += ( (x-mx)*(y-my) ) - ( (buf[i]-mx)*(buf[i+1]-my) ); } // Case: the current co-moment is NaN, so nothing to do until the buffer no longer contains NaN values... buf[ i ] = x; buf[ i+1 ] = y; return C / W; } } // EXPORTS // module.exports = incrmcovariance;